2021
DOI: 10.14416/j.asep.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Antioxidants Prevent the Degradation of Vitamin D3 Fortification in Canola Oil during Baking and In Vitro Digestion

Abstract: Vitamin D insufficiency is widespread in the northern and partly equatorial hemisphere countries. Fortification of vitamin D in commonly consumed vegetable oils can prevent rickets in children, osteoporosis and bone fractures in adults. Avoiding the loss of vitamin D3 fortification in oils during cooking is beneficial for consumer’s health. The aim of this work was to investigate the stability of cholecalciferol (vitamin D3) fortification in canola oil during baking at 80 to 230°C for 10 to 40 min. The natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The antioxidant capacity of these compounds during digestion was maintained at elevated levels. Antioxidants have been shown to protect vitamin D 3 against degradation [ 41 , 63 ]. The behaviour of vitamin D 3 during the cereal and juice digestion can be attributed to its increased release during digestion, as well as the antioxidant capacity of the phenolic acids and flavonoids present in the cereals and juice, which may have acted as protective agents against vitamin D 3 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant capacity of these compounds during digestion was maintained at elevated levels. Antioxidants have been shown to protect vitamin D 3 against degradation [ 41 , 63 ]. The behaviour of vitamin D 3 during the cereal and juice digestion can be attributed to its increased release during digestion, as well as the antioxidant capacity of the phenolic acids and flavonoids present in the cereals and juice, which may have acted as protective agents against vitamin D 3 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…However, their processing included the roasting of pork at 250 • C for 20 min followed by 150 • C until the meat core reached 80 • C. Vitamin D 3 stability studies performed in a model system by adding vitamin D 3 to the sunflower oil processed by household cooking procedures such as pan-frying, microwave, boiling, and roasting at different times and temperatures in the oven indicated a relatively little loss of 1-30% [29]. Goebel et al studied the stability of vitamin D 3 added to canola oil during baking of a dark chocolate brownie at 80-230 • C for 10-40 min by using various antioxidants [30]. They reported a vitamin D 3 loss of up to 90% when exposed to temperatures of 180-230 • C, even with the presence of antioxidants.…”
Section: Changes In the Content Of Vitamin D 3 During The Thermal Pro...mentioning
confidence: 99%
“…The decrease in vitamin D 3 bioaccessibility due to the occurrence of oxidation during digestion has also been supported by a previous study, which reported increased bioaccessibility of vitamin D 3 in brownies fortified with both vitamin D 3 and tert -butylhydroquinone, compared to a control fortified with vitamin D 3 alone. On the other hand, α-tocopherol and butylated hydroxytoluene were not efficient [ 84 ].…”
Section: Vitamin D In Fortified Foods: Bioaccessibilitymentioning
confidence: 99%